Pola komunikasi dalam mengatasi konflik antar suku Nias dan Batak Desa Tanjung Mas Kampar Kiri - Suhaimi Suhaimi; Darmawati Darmawati; M. Fahli Zatrahadi; Yurnalis Yurnalis; Miftahuddin Miftahuddin (IICET (Indonesian Institute for Counseling, Education and Therapy), 2020)
A conflict, defined as a clash of interest, derives from incompatible interactions whether individuals or groups in social entities, economic, political, and cultural activities, and in turns, conflict that arises create social instability. The current research objectives are to figure out the conflict that occurs in Tanjung Mas Village and to determine the right communication patterns in resolving existing matters. Conducted through qualitative case study, the chosen location was Tanjung Mas Village, Kampar Kiri Riau, the informants were the village head, the head of the Nias and the Batak tribes. The results obtained in this line of research demonstrated that the most common factors that lead to conflict are economic factor, the Nias people are generally stronger but receive cheaper salary than the Batak, thus an employer would prefer the Nias rather than the Batak, hence it gives way to conflict, another factor is also due to sport. In this regard, conflict resolution stages conducted by the head of the tribes is through mediation.